Product Mix at Bank Sumedang Wado Sumedang Branch - Putri Dayana; Ryan Feryana Kurniawan; Saefulrohman (Journal of Bussines Management Basic, 2022)
This study examines product mix variables that focus on deposit product at Bank Sumedang (BPR) Wado Sumedang branch. The purpose of this research is to find out the product mix as well as the constraints and solutions at Bank Sumedang (BPR) Wado Sumedang Branch. The research method used in this study is a qualitative research method using a sampling technique, namely purposive sampling. The data collection technique used is a triangulation data collection technique, which combines various data collection techniques such as observation, interviews and documentation, while in analyzing the data using the Miles and Huberman model with the following steps: data collection, data reduction, data display, and conclusion drawing data. verification. Based on the research results obtained, the implementation of the product mix at Bank Sumedang Wado Sumedang Branch is quite good, it can be seen from the product mix carried out in accordance with the provisions of the product mix dimensions, namely product mix width, product mix length, product mix depth and product mix consistency along with indicator indicator. As well as obstacles and solutions in the application of the product mix at Bank Sumedang Wado Branch occurred in several indicators of product mix dimensions but Bank Sumedang Wado Branch has made various efforts to address some of the obstacles that occur by improving the product mix strategy.